2020
DOI: 10.1590/s1678-9946202062049
|View full text |Cite
|
Sign up to set email alerts
|

Severe coronavirus infection in pregnancy: challenging cases report

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 13 publications
0
22
0
2
Order By: Relevance
“…The percentage we observed is roughly consistent with the results previously reported by Zeng et al 47 . Overall, many suspected cases have been reported thus far 11,19,23,26,[48][49][50][51][52][53][54][55][56][57] . Neonates born to infected mothers must be tested and carefully clinically monitored.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage we observed is roughly consistent with the results previously reported by Zeng et al 47 . Overall, many suspected cases have been reported thus far 11,19,23,26,[48][49][50][51][52][53][54][55][56][57] . Neonates born to infected mothers must be tested and carefully clinically monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Severe respiratory disease requiring extra-ordinary treatment or monitoring is consistently described [ 2 , 10 , 13 , 14 , 19 , 28 , 30 – 33 , 39 – 41 , 43 , 44 , 46 , 47 , 59 , 61 , 66 – 91 ]. Cardiac disease may accompany the latter [ 92 ].…”
Section: Maternal Infection With Sars-cov-2mentioning
confidence: 99%
“…A study from Spain found that nearly 50% of patients with pneumonia subsequently suffered what would have been classified as severe disease [ 86 ]. Regardless, however, COVID-19 can be directly implicated as a cause of maternal demise [ 4 , 12 , 21 , 30 , 32 34 , 39 – 41 , 44 , 47 , 68 , 72 , 76 , 80 , 88 , 93 – 98 ]. In Brazil, most such maternal deaths were occurring in the postpartum period [ 96 ].…”
Section: Maternal Infection With Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…In the new coronavirus pandemic (COVID-19), the MDSC have been reported to play an important role in the early phase of symptoms, increasing their frequency on blood in the first days of signals and symptoms, and it was related to poor outcome in severe acute respiratory syndrome in hospitalized patients. Pregnancy is a risk factor for COVID-19 severity, given the Brazilian high mortality rate of 12.7% in June 2020 withing pregnant, which may be associated with the change of the immunity [92][93][94].…”
Section: Summary Of Interferon Lambda (Ifn-λ) Function During Normal mentioning
confidence: 99%